False-Positive Heat-Damaged RBC Scan for Splenosis: Case of Retroperitoneal Extramedullary Hematopoiesis. (February 2018) - Donald, Joseph S.; Chen, Delphine L.; Peterson, Jessica; Perry, Mark
Abstract : Abstract: Extramedullary hematopoiesis (EMH) is a well-known compensatory response to severe anemia, most commonly due to a chronic hemolytic anemia such as thalassemia or sickle cell disease. We present a case of a 72-year-old man with autoimmune hemolytic anemia refractory to steroids and splenectomy. An incidental retroperitoneal mass on CT was suggestive of ectopic splenic tissue. However, an alternative diagnosis of EMH was considered, given an atypical appearance on heat-damaged 99m Tc-RBC scan, and was confirmed with biopsy. The case report illustrates the imaging characteristics of EMH, widely known to have increased activity on 99m Tc-sulfur colloid scans.